ماهية الحرب الإلكترونية في ضوء قواعد القانون الدولي - درويش، سعيد (جامعة الجزائر1 بن يوسف بن خدة, 2016)
The purpose of this research, is to study the content of the "Tallinn" Handbook, which addresses the most challenging questions, including those related to the rules of international law applicable in electronic warfare, as well as cyber-attacks carried out by States, non-state actors. This research has also for objective, to highlight related terms, such as the notion of armed conflict in the context of electronic warfare, as a cyber- fighter, cyber-actor, and the need to respect the principles of International humanitarian law during cyber war armed conflict.
تهدف هذه الورقة البحثية إلى معالجة محتوى دليل "تالين"، الذي يجيب على أهم النقاط الأساسية ذات الصلة بالحروب والهجمات الإلكترونية التي تنفذها الدول، أو تلك التي تقوم بها جهات فاعلة من دون الدول، وكذا مفهوم النزاع المسلح في إطار الحرب الإلكترونية، بالإضافة إلى مفهوم الجيوش الإلكترونية وكيفية إدارة الحرب الإلكترونية، من خلال التطرق لقواعد الاشتباك الإلكتروني فضلا عن صفة المقاتل الإلكتروني، وأخيرا ضرورة مراعاة مبادئ القانون الدولي الإنساني المعروفة كمبدأ التمييز مثلا، ومسألة شرعية استهداف المقاتل الإلكتروني بالوسائل العسكرية المادية، كالطائرات العسكرية من دون طيار وغيرها.
Keywords: الحرب الإلكترونية -- القانون الدولي -- الجرائم الإلكترونية -- تقنية الانترنت